phenix.mr_rosetta: molecular replacement and model rebuilding with Phenix and Rosetta - Terwilliger, Thomas C.; DiMaio, Frank; Read, Randy J.; Baker, David; Bunkóczi, Gábor; Adams, Paul D.; Grosse-Kunstleve, Ralf W.; Afonine, Pavel V.; Echols, Nathaniel (Journal of structural and functional genomics, 2012)
The combination of algorithms from the structure-modeling field with those of crystallographic structure determination can broaden the range of templates that are useful for structure determination by the method of molecular replacement. Automated tools in phenix.mr_rosetta simplify the application of these combined approaches by integrating Phenix crystallographic algorithms and Rosetta structure-modeling algorithms and by systematically generating and evaluating models with a combination of these methods. The phenix.mr_rosetta algorithms can be used to automatically determine challenging structures. The approaches used in phenix.mr_rosetta are described along with examples that show roles that structure-modeling can play in molecular replacement.